2020
DOI: 10.1007/978-3-030-44999-5_28
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Ivory Tower: A Meta Model for Staged Maturity Models

Abstract: When it comes to the economic and strategic development of companies, maturity models are regarded as silver bullets. However, the existing discrepancy between the large amount of existing, differently developed models and their rare application remains astonishing. We focus on this phenomenon by analyzing the models' interpretability and possible structural and conceptual inconsistencies. By analyzing existing, staged maturity models, we develop a meta model for staged maturity models so different maturity mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The results are positioned in the context of digitalization and Industry 4.0 as an area characterized by unpredictable dynamics that continuously change what can be considered the status quo (Verhoef et al, 2021). To successfully cope with this organizational transformation, maturity models focusing on digitalization and Industry 4.0 have emerged as useful tools (Bley et al, 2020). The comprehensive review by Caiado et al (2021) identified a total of 24 models, of which only 5 (Asdecker & Felch, 2018, Rübel et al, 2018, Schumacher et al, 2016, Scremin et al, 2018, Weber et al, 201720.8 %) rely on a procedure model for model design (see Table 4 and Appendix E).…”
Section: Citation Context Analysis: Resultsmentioning
confidence: 99%
“…The results are positioned in the context of digitalization and Industry 4.0 as an area characterized by unpredictable dynamics that continuously change what can be considered the status quo (Verhoef et al, 2021). To successfully cope with this organizational transformation, maturity models focusing on digitalization and Industry 4.0 have emerged as useful tools (Bley et al, 2020). The comprehensive review by Caiado et al (2021) identified a total of 24 models, of which only 5 (Asdecker & Felch, 2018, Rübel et al, 2018, Schumacher et al, 2016, Scremin et al, 2018, Weber et al, 201720.8 %) rely on a procedure model for model design (see Table 4 and Appendix E).…”
Section: Citation Context Analysis: Resultsmentioning
confidence: 99%
“…A MM describes the development of capabilities for a domain in a discrete sequence of maturity levels (Becker et al, 2009;Stelzl et al, 2020). MMs consist of several central constructs for which no uniform terminology exists in the literature (Bley et al, 2020;Lasrado et al, 2015;Stelzl et al, 2020). Therefore, an understanding of the terminology used in this paper relating to the MM meta-model by Bley et al (2020) is shown in Table 1.…”
Section: Maturity Modelmentioning
confidence: 99%
“…Therefore, we discuss and elaborate the characteristics of a digital BP as Information Systems Design Theory according to Gregor and Jones as it "allows the prescription of guidelines for further artifacts of the same type" [7]. Thus, we provide the entirety of components relevant for the theoretical and conceptual functionality of a digital BP and thereby offer primarily prescriptive statements about its development process [17]. Figure 2 offers an overview of our research.…”
Section: Conceptual Approachmentioning
confidence: 99%